RECALLING FIELDWORK. A BOOK ON THE INTERSECTIONS OF INTIMACY, BOUNDARIES, INTERPRETATIONS AND POWER - Maria CERNAT (Association of Social and Educational Innovation, 2024)
This review critically examines the book titled "Recalling Fieldwork: People, Places, and Encounters," edited by Raluca Mateoc and François Rüegg. The book presents an invaluable collection of memories shared by prominent anthropologists, who utilize it as a platform for meta-discursive analysis of their professional development and the pivotal role of fieldwork in their research endeavors. This review meticulously engages with the diverse anthropological narratives presented within the book, scrutinizing the researcher- source relationships and unveiling potential latent political underpinnings inherent to this scholarly undertaking. By closely examining the rich content of the book, this review contributes to a deeper understanding of the intricate interplay between personal experiences, academic growth, and the broader socio-political contexts that shape the discipline of anthropology.